Kajian Literatur: Aktivitas Antibakteri dari Ekstrak Daun Sirih (Piper betle L.) Terhadap Bakteri Staphylococcus aureus - Nur Amrillah; Ramadhan Triyandi; Muhammad Iqbal; Citra Yuliyanda Pardilawati (CV. Jasa Sukses Abadi, 2023)
Bacterial infection is a major health problem that affects many humans. The therapy used to treat bacterial infections generally uses antibiotics. However, the inappropriate and continuous selection and use of antibiotics can lead to the occurrence of antibiotic resistance in humans. Staphylococcus aureus is one of the most involved pathogenic bacteria in human bacterial infections. This bacterium is found in the normal skin microbiota of animals and humans. Staphylococcus aureus has infected as many as 20-30% of the healthy human population. Staphylococcus aureus produces antibiotic neutralizing enzymes resulting in resistance to many antibiotics. Many developing countries use medicinal plants as an alternative to treat infections. More than 700 species of betel leaf are found in the North and South of the world and are widely grown in most countries such as Indonesia, India, Sri Lanka, Malaysia, the Philippines, as well as other countries in Southeast Asia and East Africa. Boiled betel leaf (Piper betle L.) has been widely used in Indonesia as an alternative medicine. Betel leaf extract contains several chemical components such as terpenoids, alkaloids and phenolic compounds such as flavonoids, tannins and saponins. These components are known to have strong potential as antibacterial. This study article aims to find out whether betel leaf extract (Piper betle L.) has the ability to inhibit bacterial growth and what concentration of the extract is needed so that there is inhibition of activity and growth of Staphylococcus aureus.